Dari Dewa Menjadi Pahlawan Budaya Populer : Analisis Naratif Desakralisasi dalam Serial Televisi Percy Jackson and the Olympians dan Film Shazam! Fury of the Gods - Lapalelo, Putra Aditya; Chandra, Christoper; Liwang, Grishiella Patricia (Jurnal Sosial-Politika, 2025)
Superhero films have long been popular because they play a role in shifting the sacred boundaries of a culture. Things that were once taboo to consume are now, through superhero films, popular cultural products that are consumed without sacred boundaries. This concept is popularly known as cultural desacralization. To examine this, the study analyzes two superhero and god-themed films, the TV series Percy Jackson and the Olympians and the film Shazam! Fury of the Gods, to see how the narrative of cultural desacralization is carried out in superhero films. The results concluded that the process of desacralization that occurred in the TV series Percy Jackson and the Olympians and the film Shazam! Fury of the Gods was a form of desacralization that involved economic commodification and the transformation of sacred socio-cultural values to make them more acceptable to a wider audience. On the one hand, the filmmakers placed morality in accordance with the common agreement of society, with the aim of attracting the consumer interest of the public towards the two films. On the other hand, the films also contain representative messages. Thus, the process of desacralization is not only read as an object of commodification. It is also seen as a form of cultural distribution, through the transformation of desacralization, where information that was once sacred is now opened up and disseminated through films in the hope that people will be interested.